Improvements in thermal efficiency of onion slice drying by exhaust air recycling. Issue 1 (1st January 2021) - Djaeni, Mohamad; Hadiyanto, Hadiyanto; Kumoro, Andri Cahyo; Utari, Febiani Dwi; Hii, Ching-Lik
Abstract: Drying is an important process that extends the storage life and retains the quality of onion. Unfortunately, convective dyers with poor engineering designs and construction show low thermal efficiency for onion drying. This work aims to study the effects of recycled exhaust air on the thermal efficiency of onion slice drying at various temperatures and drying capacities. The exhaust air leaving the drying chamber was recirculated and mixed with fresh air to reduce the preheating load. The thermal efficiency of the proposed system was calculated and compared with the results of a standard drying process without exhaust air recycling. Findings showed that the average thermal efficiency of the modified dryer improved with increasing drying temperature, drying capacity, and recycled exhaust air-to-fresh air ratio. Optimization via a central composite design revealed an optimal thermal efficiency of 58.82% at a drying temperature of 67.94°C, drying capacity of 0.089 kg of onion slices, and recycled exhaust air-to-fresh air ratio of 4.0. The findings of this work suggest that significant cost reduction in onion slice drying may be achieved by optimizing the recycled exhaust air-to-fresh air ratio and drying capacity of the dryer.